Dynamics of MHD second-grade nanofluid flow with activation energy across a curved stretching surface - Reddy, Srinivas C.; Asogwa, Kanayo Kenneth; Yassen, Mansour F.; Adnan; Iqbal, Zahoor; M-Eldin, Sayed; Ali, Bagh; KM, Swarnalatha (Frontiers in Energy Research, 2022)
This analysis addresses the influence of activation energy on the MHD flow of second-grade nanoliquid over a convectively heated curved stretched surface. The impact of heat generation/absorption, thermophoresis and Brownian motion are also incorporated. This current study in addendum reveals the solution narrating the nanofluid flow behaviour of the stretched curve to better the performance of the system. hence, the mathematical construction of governing partial differential equations (PDEs) is transmitted into nonlinear ODEs by employing appropriate transformations. The attained ODEs are conducted numerically via ND-Solve. It is consequential to report that fluid velocity and temperature fields significantly rise with concurrent enhancing values of the fluid parameter and curvature parameter. Moreso, The concentration field enhances considering energy activation variable and suppresses with the reaction rate constant while thermophoresis escalates the temperature distribution as the Nusselt number lowers with a stronger internal heat source parameter Q.